Myeloid Sarcoma: An Unusual Presentation of Acute Promyelocytic Leukemia Causing Spinal Cord Compression - Kyaw, T.Z.; Maniam, J.A.S.; Bee, P.C.; Chin, E.F.; Nadarajan, V.S.; Shanmugam, H.; Abd Kadir, K.A. (Galenos Yayinevi, 2012)
Acute promyelocytic leukemia with concurrent myeloid sarcoma is a rare clinical event. Herein we describe a patient that presented with back pain and bilateral leg weakness caused by spinal cord compression due to extramedullary deposition of leukemic cells. Acute promyelocytic leukemia was suspected based on immunophenotypic findings of malignant cells in bone marrow aspirate. The diagnosis was confirmed by the presence of PML-RARα fusion copies. MRI showed multiple hyperintense changes on the vertebral bodies, together with intraspinal masses causing spinal cord compression. The patient immediately underwent radiotherapy, and was treated with all-trans retinoic acid and idarubicin. Reassessment MRI showed complete resolution of all intraspinal masses and the disappearance of most of the bony lesions. Post-treatment bone marrow aspirate showed complete hematological and molecular remission. The motor power of his legs fully recovered from 0/5 to 5/5; however, sensory loss below the T4 level persisted.